Pengaruh Reputasi Perusahaan dan Kualitas Pelayanan Terhadap Keputusan Pemilihan Event Organizer PT Genindo Pro Indonesia - Fernando Turnip, Hilarius Holfedner; Benazira, Aulia (Abdimas Indonesian Journal, 2025)
The large number of event organizers in the city of Medan makes competition in this business increasingly tight, this makes event organizers strive to improve the company's reputation and the quality of its services. This research aims to find out whether the company's reputation and service quality influence the decision to select event organizer PT Genindo Pro Indonesia. The population of this study was 43 people and the sample used was 43 respondents (saturated). Data collection was carried out through questionnaires distributed in the form of Google forms via social media and through literature studies in the form of primary and secondary data. This research uses quantitative research methods with descriptive research types which include validity testing, reliability testing, classical assumption testing, hypothesis testing. The results of this research are (1) the company reputation variable partially influences the selection decision with a t-count value of 2,964, (2) the service quality variable partially influences the selection decision with a t-count value of 3,039, (3) the company reputation and service quality variables simultaneously influence election decisions. The research results from the coefficient of determination test (R2) show that the service and facility quality variables are able to influence selection decisions by 62,3% and the remaining is 37,7% influenced by other variables not examined in this research.